Aspects of the plasma biochemistry and tibia minerals of broilers fed amorphous dolomite as a natural source of calcium and magnesium - GEORGETA, CIURESCU; ANCA, GHEORGHE; ELIZA, MARIN DANIELA; ELENA, UNTEA ARABELA (The Indian Journal of Animal Sciences, 2014)
One-day-old Cobb 500 broiler chicks (1200) were allocated to 3 experimental treatments, each one had 4 replicates. The treatments differed only by the source of Ca and Mg supplemented as follows: control group contained limestone (as Ca source: 10.0/9.6/9.0 g/kg, for each growth phases) and MgO (as Mg source: 2.36/2.39/ 2.38 g/kg, for each growth phases); AD1 and AD2 groups – limestone and MgO were replaced with AD as Ca and Mg source. The AD1 diet contains the same levels of Ca as control and Mg levels were 5.8/5.6/5.45 g/kg. The AD2 diet contained reduced levels of Ca (7.5/7.3/6.8 g/kg) and Mg levels were 4.3/4.21/4.12 g/kg, for each of the growth phases. The plasma biochemistry was not influenced by treatments, except Mg concentration which was increased in the experimental groups. Tibia ash, bone Ca and P content were not different in any of the treatment groups. Bone Mg content was increased in the AD groups compared with control. AD can improve weight gain and presented similar plasma metabolic profile, tibia ash and bone Ca and P content with limestone adding MgO.